Service organizations in China: reforms and institutional constraints - Lam Tao-chiu; Perry, James L. (2001)
This article examines a neglected area of reform in China: service organizations. It discusses the structural features of service organizations and the institutional constraints on efforts to reform them. - Reproduced
Keywords: Administrative reform - China; Administrative reform